Topographical organization of the afferents to the Nucleus Accumbens of the Rat : A Horseradish Peroxidase study - Jiamjit Sangsuwan (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm.)--Chulalongkorn University, 1984